Factors Related to Non-Referral of Patients with Presumptive Pulmonary TB to Designated Microscopy Centers (DMCs) by Registered Private Practitioners in Urban Areas of Punjab, India - Sharma, Sarit (J Clin Diagn Res, 2015)
BACKGROUND: Early diagnosis and proper treatment under RNTCP guidelines, forms the mainstay of management of a TB patient. A large proportion of patients with presumptive tuberculosis (TB) visit a Private Practitioner (PP) in the first place. Studies have shown that PPs rely more on X-rays and other diagnostic tools rather than referring the patient to the nearest Designated Microscopy Centre (DMC) for sputum microscopy. AIM: The present study was planned to look in to factors responsible for non-referral of patients with presumptive pulmonary TB to the DMCs for diagnosis by PPs. MATERIALS AND METHODS: Present study was a case-control study conducted over a period of one year among registered PPs in urban areas of Punjab. The study was carried out in five major cities which have approximately half of the urban population of Punjab. Forty three Private Practitioners per city for referral group and 43 matched PPs for non-referral group were selected. RESULTS: Knowledge regarding RNTCP was low in both the referral (38.1%) as well as non-referral (25.6%) group of PPs. Allopathic doctors had significantly higher knowledge regarding TB as compared to ayurvedic and homeopathy doctors, and Registered Medical Practitioners (RMP). Both the knowledge of PPs regarding nearest DMC as well as perception about accessibility of the nearest DMC for the patients were found to be significantly higher in the referral group. Only 15.3% of practitioners in the non-referral group said that they had been contacted by RNTCP staff. CONCLUSION: The main factors responsible for non-referral of pulmonary TB suspects to DMCs for diagnosis in the present study included low knowledge regarding RNTCP, lack of awareness regarding place and accessibility of nearest DMC, and inadequate sensitization of PPs by the RNTCP staff.